PTH-139 Gastrin now: establishing a trainee led research network. (8th June 2018) - Nixon, Kirsty; White, Katherine; Gashau, Wadiamu; Morris, Liam; Kalla, Rahul; Borg–Bartolo, Simon
Abstract : Introduction: Research, quality improvement and audit are essential parts of effective personal and professional development. Increasing clinical demands and the proposed shortening of training time may limit trainees' involvement in clinical research. Trainee led research and improvement networks (TLRINs) allow us to develop large, cost-effective, multi-site quality improvement and research projects without necessitating time out of programme. They also provide opportunities for tailored input dependent on personal clinical interest. Aims: To assess the feasibility of a new TLRIN, GasTRIN NoW, within Health Education England North West, by conducting a multi-site clinical audit. We aimed to recruit trainee members from 75% of 16 potential hospital sites, and from these obtain 75% complete data. Methods: Membership was offered to all gastroenterology specialty trainees in the North West Deanery. All consultants were offered honorary membership. We replicated an audit proforma from the West Midlands TLRIN (GARnet) to assess the management of acute upper gastrointestinal bleeds, collecting prospective data over a one month period. Members were required to sign a constitution to ensure fair acknowledgment of work. Video conferencing enabled regular committee meetings with additional updates to members at regional gastroenterology teaching days. Results: Led by a committee of 6 trainee members, 27 trainees, supported by 25 consultants, from 13 sites (81%) were recruited to GasTRIN NoW. Complete audit data were received from 10 sites (77%). Conclusion: The need for and utilisation of TLRINs is increasing in gastroenterology. TLRINs offer trainees the opportunity to experience research and quality improvement in a peer-supported environment alongside clinical work. This will allow them to achieve competencies required for successful attainment of CCT and become more rounded consultants of the future. TLRINs provide a cost effective approach to answer questions of clinical importance and provide innovative change in a coordinated manner. Continuity for data collection and project structure exists even when trainees rotate hospital placements. Our current model has produced encouraging results, building a comprehensive and comparable picture of practice throughout the region with no financial requirements in initial set up.